1978
DOI: 10.1210/jcem-47-3-480
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Affects Basal and Augmented Pituitary Hormone Secretion*

Abstract: Although the role of the neurotransmitter, dopamine (DA), in the regulation of PRL has been well documented, controversy exists regarding its participation in the regulation of the other pituitary hormones. Consequently, we infused DA into six healthy male subjects (ages 19-32) and studied its effects on both basal pituitary hormone levels and augmented hormonal release induced by insulin hypoglycemia (ITT), TRH, and gonadotropin-releasing hormone (GnRH). DA alone produced a modest though significant increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
75
2
2

Year Published

1980
1980
1987
1987

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(89 citation statements)
references
References 40 publications
10
75
2
2
Order By: Relevance
“…The rise in GH produced by amphetamine does not differ between the (+) and (-) isomers (Langer & Matussek, 1977) and this, together with the fact that the effect is not blocked by pimozide suggests that this response is noradrenergic (Sachar, Gruen, Altman, Halpern & Frantz, 1976). Dopamine infusion has been reported to increase the secretion of GH in some studies (Burrow, May, Spaulding & Donabedian, 1977, Leebaw et al, 1978 Increases synthesis of dopamine and noradrenaline and 5-HT 'Indirect presynaptic agent-releases biogenic amines,-noradrenaline and dopamine and blocks re-uptake-increase in turnover of dopamine, noradrenaline and ? 5-HT.…”
Section: Anxiolyticsmentioning
confidence: 87%
“…The rise in GH produced by amphetamine does not differ between the (+) and (-) isomers (Langer & Matussek, 1977) and this, together with the fact that the effect is not blocked by pimozide suggests that this response is noradrenergic (Sachar, Gruen, Altman, Halpern & Frantz, 1976). Dopamine infusion has been reported to increase the secretion of GH in some studies (Burrow, May, Spaulding & Donabedian, 1977, Leebaw et al, 1978 Increases synthesis of dopamine and noradrenaline and 5-HT 'Indirect presynaptic agent-releases biogenic amines,-noradrenaline and dopamine and blocks re-uptake-increase in turnover of dopamine, noradrenaline and ? 5-HT.…”
Section: Anxiolyticsmentioning
confidence: 87%
“…Therefore, it seems that DA has a OH stimulating effect via ME when L-dopa was administered exogenously, although it has not such effect in basal state. It is suggested that DA stimulates GHRH release from the GHRH nerve terminals present in ME (Martin 1973;Leebaw et al 1978;Bansal et al 1981). The fact that DA infusion causes OH increase lends a support to the above explanation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also stimulated by the combined administration of L-dopa plus carbidopa (DOPA-decarboxylase inhibitor) which elevates the CNS DA concentration by blocking the conversion of peripheral L-dopa to DA (Bansal et al 1981). In addition, DA infusion increases plasma GH secretion, although DA is known not to cross BBB (Burrow et al 1977; Leebaw et al 1978;Bansal et al 1981). Therefore, it seems that DA and DA-agonists have stimulatory effects on GH secretion either at the level of CNS (hypothalamus) or periphery (median eminence (ME) and pituitary gland).…”
mentioning
confidence: 99%
“…In addition, it has been reported that dopamine has dual actions on OH release in man ; a releasing effect via the hypothalamus and a direct inhibitory effect on the pituitary gland (Tallo and Malarkey 1981; Marcovitz et al 1982). Therefore, it is plausible that dopamine stimulates the OH releasing factors from peptidergic GH-RF neurons at the level of the median eminence which lies outside of the blood brain barrier (Martin 1973; Leebaw et al 1978;Bansal et al 1981). From these considerations, the difference in the rebound increase between acromegalic patients and normal controls can be explained by a difference in the regulations of OH release by the hypothalamus and somatotrophs having different dgrees of binding and dissociation of 0TH.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acepted that human pituitary hormones are apt to show rebound increases after the administration of inhibitory agents (Hall et al 1973 ; Besser et al 1974a; Leblanc et al 1976;Judd et al 1978; Leebaw et al 1978 ; Kaptein et al 1980). Although the exact mechanism is not studied well, the rebound could be due to (1) increased hypothalamic releasing factors; (2) decreased hypothalamic inhibiting factors ; or (3) an overshoot from the stored pituitary pool (Martin 1976 ;Judd et al 1978;Hanew and Rennels 1982).…”
mentioning
confidence: 99%